THE COMPLEX OF HUE MONUMENTS: A HISTORICAL AND CULTURAL TREASURE OF VIETNAM - Olimov, Kozimjon (Educational Research in Universal Sciences, 2023)
The Complex of Hue Monuments, located in the central region of Vietnam, is a UNESCO World Heritage site renowned for its rich historical and cultural significance. This scientific article provides a comprehensive overview of the Hue Monuments, exploring their architectural marvels, historical context, cultural value, and the efforts taken for preservation and conservation. The site’s profound legacy offers valuable insights into Vietnam’s past and continues to be a source of inspiration for cultural heritage preservation worldwide.